Perception of police by local in Manipur - ROSHINI, DR. MOIRANGTHEM (The journal of contemporary issues in business and government, 2021)
Police are regarded as the most important job as it helps in guiding us from all the wrong doers. They act as a mirror of the society . They help in reducing the crime rate of the place and also help in bringing justice to the system. They play a major role in reforming the negative vibes to positive vibes for the people and their satisfaction. Manipur , a state in North east of India face end number of issues every day which ultimately lead to solving with police. In this case police need to make a good image and should understanding with people so that they are connected with them. This paper focus on how police perform their duty to give 100% to the society. Questionnaire were prepared to have direct interaction with the respondents. Tabulation and pie chart were made to analyse the questions in detail.